2016
DOI: 10.1111/disa.12173
|View full text |Cite
|
Sign up to set email alerts
|

The Four Cs of disaster partnering: communication, cooperation, coordination and collaboration

Abstract: Public, nonprofit and private organisations respond to large-scale disasters domestically and overseas. Critics of these assistance efforts, as well as those involved, often cite poor interorganisational partnering as an obstacle to successful disaster response. Observers frequently call for 'more' and 'better' partnering. We found important qualitative distinctions existed within partnering behaviours. We identified four different types of interorganisational partnering activities often referred to interchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 35 publications
0
77
0
Order By: Relevance
“…The importance of relationships, and especially preexisting relationships, was evident during the response to the 2010 Haiti earthquake. Martin, Nolte, and Vitolo (2016) identified that even though local knowledge was recognized as an essential attribute for collaborative disaster response to occur, there were challenges integrating local government and local nonprofit organizations into the overall emergency management arrangements. The collaborative relationships that were successful had preexisting interaction before the disaster and continued to enhance their collaborative relationships during the response (Martin et al, 2016).…”
Section: Response Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of relationships, and especially preexisting relationships, was evident during the response to the 2010 Haiti earthquake. Martin, Nolte, and Vitolo (2016) identified that even though local knowledge was recognized as an essential attribute for collaborative disaster response to occur, there were challenges integrating local government and local nonprofit organizations into the overall emergency management arrangements. The collaborative relationships that were successful had preexisting interaction before the disaster and continued to enhance their collaborative relationships during the response (Martin et al, 2016).…”
Section: Response Phasementioning
confidence: 99%
“…Martin, Nolte, and Vitolo (2016) identified that even though local knowledge was recognized as an essential attribute for collaborative disaster response to occur, there were challenges integrating local government and local nonprofit organizations into the overall emergency management arrangements. The collaborative relationships that were successful had preexisting interaction before the disaster and continued to enhance their collaborative relationships during the response (Martin et al, 2016). The importance of partnerships in building collaborative relationships is also evident in the literature exploring collaboration in the recovery phase of disasters.…”
Section: Response Phasementioning
confidence: 99%
“…Stakeholders may take the view that emergency preparedness is not justified, given its high cost, and perceive that disasters are unexpected and are not likely to occur (Young and Jones 2016). Moreover, there is a lack of interorganisational co-ordination especially during the response phase of EM; ambiguous lines of authority; inconsistent and inefficient communication within and between stakeholders; and disorganised communities (Cho and Poister 2013;Martin, Nolte and Vitolo 2016;Ramli, Mokhtar and Aziz 2014). What emerges from these obstacles is that EM is often reactionary in response to disaster events, and that there is significant scope for HRM interventions to enhance the capacity of EM (Young and Jones 2016).…”
Section: Obstacles That Impact On Emmentioning
confidence: 99%
“…The literature shows that there is an increasing need for intra-and inter-organizational interaction, not least because of several major drivers. Growing interdependencies, rapid technological change, increased expectations for integrated services, increased complexity and uncertainty, including the immediate imperative to respond to crisis and unexpected events (Comfort, 2007;Ansell et al, 2010;Boston and Gill, 2011;Martin et al, 2016;Torgersen, 2018b). The emphasis on interaction comes from a greater recognition that the existing institutional apparatus is not sufficient to handle increasingly complex and ambiguous societal challenges, such as unforeseen events, which in turn challenge patterns of organizations by transcending organizational boundaries (Ansell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also positioned the four dimensions cooperation, coordination, collaboration and service integration in a continuum based on high integration and little autonomy (Selden et al, 2006). From research on crisis management Martin et al (2016) found important qualitative distinctions between the fours Cs; communication, cooperation, coordination and collaboration. The four terms represent a continuum of increased interorganizational embeddedness in partnering activities (Martin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%